Chapter Coastal heritage and territorial signs - Ivona, Antonietta (Proceedings e report, 2020)
Geographical space must be understood as a progressive and conscious construction in which the geographical elements and the relationships between the elements themselves are placed. From the post-World War II period and for the following twenty years, the coastal area has maintained an albeit minimal break with the man-made spaces; since the seventies of the last century, rapid industrial development has increasingly occupied the coasts. Among the most evident coastal territorial signs are the lighthouses. The analysis intends to reflect on the path of transformation of some coastal structures in Italy.